Analytical, experimental and numerical study of timber-concrete composite beams for bridges - Molina, Julio C. [UNESP]; Junior, Carlito Calil; De Oliveira, Diego R.; Gomes, Nádia B. [UNESP] (My University, 2019)
In this study, the strength and stiffness (EI) of wood-concrete composite beams for bridges with T-shaped cross section were evaluated. Two types of connectors were used: connectors bonded with epoxy adhesive and connectors attached to the wood just by pre-drilling (without adhesive). The connectors consisted of common steel bars with a diameter of 12.5 mm. Initially, the strength and stiffness (EI) of the beams were analyzed by bending tests with the load applied at the third point of the beam. Subsequently, the composite beams were evaluated by numerical simulation using ANSYS software with focus on the connection system. To make the composite beams, Eucalyptus citriodora wood and medium strength concrete were used. The slip modulus K and the ultimate strength values of each type of connector were obtained by direct shear tests performed on composite specimens. The results showed that the connector glued with epoxy adhesive resulted in better strength and stiffness (EI) for the composite beams when compared to the connector fixed by pre-drilling. The differences observed were up to 10%. The strength and stiffness (EI) values obtained analytically by Möhler’ model were lower than the values obtained experimentally from the bending tests, and the differences were up to 25%. The numerical simulations allowed, with reasonable approximation, the evaluation of stress distributions in the composite beams tested experimentally.
Keywords: Analytical Möhler model; Composite beams; Numerical simulation; Steel bar connector; Stiffness EI; Strength; Timber-concrete